An open‐label randomized study of the relative absorption of gastro‐resistant risedronate taken fasted or with food versus immediate‐release risedronate - Diane Kleinermans; Andrew Joyson; Heather Wray (Wiley, 2022)
Abstract Patients with osteoporosis often take oral bisphosphonates with food, rendering these medications ineffective. This study compared the relative absorption of four formulations of gastro‐resistant (GR; formulations 1-4) risedronate 35 mg versus immediate‐release (IR) risedronate 35 mg taken fasted. Secondarily, it compared the relative absorption of GR formulations administered fed and fasted, and determined the site of disintegration. Healthy participants (N = 160) were randomized to one of nine treatment groups: IR risedronate taken fasted (group A) or formulations 1-4 taken fasted or fed (groups B-I). Fasted groups fasted for 8 h pre‐dose and 4 h post‐dose. Fed groups fasted for 7.5 h, then took risedronate with breakfast. Urine was collected until 72 h post‐dose and analyzed using liquid chromatography. From each group, up to seven participants underwent scintigraphic monitoring to assess tablet disintegration. The percentage of total dose recovered in urine (A'e) was ~0.5% for group A. The A'e of formulations 1-4 taken fasted was 0.220% (90% confidence interval 0.124-0.389), 0.298% (0.122-0.730), 0.154% (0.090-0.264), and 0.108% (0.051-0.231), respectively. With food, the A'e of formulation 1 decreased least versus fasted (−27%) compared with the A'e of formulations 2, 3, and 4 (−73%, −80%, and −65%, respectively). Formulations 1-3 disintegrated in the small intestine, formulation 4 closer to the large intestine. All GR formulations were well tolerated and in line with the known safety profile for IR risedronate. Formulation 2 had the highest absorption when taken fasted, whereas the absorption of formulation 1 was least affected by food.